LEGAL STRATEGY TO PROTECT CHILDREN'S EDUCATIONAL RIGHTS THROUGH CSR: WHY IS IT NEEDED AND HOW IS IT IMPLEMENTED? - Anastya Putri; Hari Sutra Disemadi (Legal Spirit, 2022)
Corporate Social Responsibility (CSR) is the Company's commitment to participate in sustainable economic development to improve the quality of life and the environment that is beneficial, both for the Company itself, the local community, and society in general. One sector that is an essential component in implementing CSR is education. This study aims to describe CSR policies as a legal strategy to protect children's education rights. This research uses normative juridical research with a statutory approach. The results obtained in this study are that the Indonesian government guarantees the protection of children's education rights by implementing a CSR policy. CSR implementation in Indonesia is regulated in Indonesian Law number 40 of 2007 concerning Limited Liability Companies. Article 74 paragraph (1) states that companies whose businesses are in the field and/or related to natural resources are obliged to carry out CSR. Therefore, the progress of the world of education cannot run alone, so there is a need for cooperation between companies, communities, and governments through CSR programs.